A fuzzy logic controller with fuzzy scaling factor calculator applied to a nonlinear chemical process - Anzalone, Alessandro; Iglesias, Edinzo; García, Yohn; Smith, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia)
A combined fuzzy controller, consisting of a conventional fuzzy logic controller (FLC) with a fuzzy output scaling factor calculator that modifies the scaling factor of the FLC, is proposed. The performance of this controller is compared to the performance of a PID controller and a conventional FLC for disturbance rejection in a nonlinear chemical process. The proposed controller maintains its robustness under conditions at which performance of the other controllers decay.